2011
DOI: 10.1128/aac.00998-10
|View full text |Cite
|
Sign up to set email alerts
|

Spread of the qnrVC Quinolone Resistance Determinant in Vibrio cholerae

Abstract: We read with great interest the recently published paper by Kim et al. (3) that reported a new qnr gene cassette, qnrVC3, inserted in the mobile integrative conjugative element SXT, found in Vibrio cholerae. qnrVC3 presented 99% identity to the first described qnr gene cassette (qnrVC1) found in a V. cholerae strain (VC627) from Brazil, reported by us (2). After publication of the qnrVC3 sequence, we verified that the submitted qnrVC1 sequence, in fact, did not contain the mismatches that raised the amino aci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 4 publications
0
1
0
Order By: Relevance
“…Antibiotic resistance could be simultaneously shown against three antibiotic classes (beta-lactams, for example, penicillin, cephalosporin, and carbapenem; polymyxins; and sulfonamides) for five seafood-associated NOVC (16-VB00021, 16-VB00024, 16-VB00025, 17-VB00441, and 19-VB00051). Relevant gene distribution could explain some results from antibiotic in vitro assays, including blaCARB presence and AMP resistance [73,74], almG presence and COL resistance [75], qnrVCs presence and quinolone (CIP and NAL) resistance [76], varG and IMIPEN resistance [77], and dfrA31 presence and TMP resistance [78]. However, AST result cannot be fully explained by genetic information: the COL resistance rate is 87%, while all NOVC strains used in this study contain almG; blaCARB was not found in the three AMP resistant strains; and all catB9 harboring strains have no in vitro resistance to CHL.…”
Section: Antimicrobial Resistance Abilitymentioning
confidence: 99%
“…Antibiotic resistance could be simultaneously shown against three antibiotic classes (beta-lactams, for example, penicillin, cephalosporin, and carbapenem; polymyxins; and sulfonamides) for five seafood-associated NOVC (16-VB00021, 16-VB00024, 16-VB00025, 17-VB00441, and 19-VB00051). Relevant gene distribution could explain some results from antibiotic in vitro assays, including blaCARB presence and AMP resistance [73,74], almG presence and COL resistance [75], qnrVCs presence and quinolone (CIP and NAL) resistance [76], varG and IMIPEN resistance [77], and dfrA31 presence and TMP resistance [78]. However, AST result cannot be fully explained by genetic information: the COL resistance rate is 87%, while all NOVC strains used in this study contain almG; blaCARB was not found in the three AMP resistant strains; and all catB9 harboring strains have no in vitro resistance to CHL.…”
Section: Antimicrobial Resistance Abilitymentioning
confidence: 99%